Adherence to optimal medical therapy and control of cardiovascular risk factors in patients after ST elevation myocardial infarction in Mexico - Villalobos-Pedroza, Montserrat; Hernandez-Pastrana, Sarai; Arias-Mendoza, Alexandra; Latapi-Ruiz Esparza, Ximena; Robles-Ledesma, Mariana; Guerrero-Ochoa, Alejandra; Milanes-Gonzalez, Nelson Antonio; Solis-Jimenez, Fabio; Sierra Gonzalez-De Cossio, Alejandro; Flores-Batres, Alejandro Pablo; Brindis-Aranda, Arielle Astrid; Rivera-Pedrote, Edgar; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction In developing countries, there is a notable scarcity of real-world data on adherence to optimal medical therapy (OMT) and its correlation with major cardiovascular adverse events (MACEs) after ST-elevation myocardial infarction (STEMI). Our study focuses on addressing this gap by evaluating adherence to OMT, examining its influence on the risk of MACEs after STEMI, and assessing subsequent cardiovascular risk factor control in Mexico. Methods We conducted a prospective observational study of post-STEMI patients after hospital discharge. Adherence to treatment was assessed over a median of 683 days (interquartile range: 478–833) using the Simplified Medication Adherence Questionnaire (SMAQ). Patients were followed up for 4.5 years to monitor MACEs (cardiovascular death, cardiogenic shock, recurrent myocardial infarction, and heart failure). Results We included 349 patients with a mean age of 58.08 years (±10.9), predominantly male (89.9%). Hypertension (42.4%), smoking (34.3%), type 2 diabetes mellitus (31.2%), obesity (22.92%), and dyslipidemia (21.4%) were highly prevalent. Adherence to OMT per SMAQ was 44.7%. The baseline clinical characteristics of adherent and non-adherent patients did not significantly differ. OMT prescription rates were as follows: acetylsalicylic acid, 91.1%; P2Y12 inhibitors, 76.5%; and high-intensity statins, 86.6%. While non-adherent patients had a numerically higher rate of MACEs (73 vs. 49 first events), there was no statistically significant difference (hazard ratio 1.30, 95% confidence interval 0.90–1.88). Discussion In this real-world study of patients after STEMI, we observed low adherence to OMT, a low proportion of global cardiovascular risk factor control, and a numerically higher incidence of recurrent major adverse cardiovascular events in non-adherent patients. Strategies to improve adherence to OMT and risk factor control are needed.